Structural factors and best practices in implementing a linkage to HIV care program using the ARTAS model - Craw Jason; Gardner Lytt; Rossman Amber; Gruber DeAnn; Noreen O'Donnell; Jordan Diana; Rapp Richard; Simpson Cathy; Phillips Karen (BMC, 2010)
Abstract Background Implementation of linkage to HIV care programs in the U.S. is poorly described in the literature despite the central role of these programs in delivering clients from HIV testing facilities to clinical care sites. Models demonstrating success in linking clients to HIV care from testing locations that do not have co-located medical care are especially needed. Methods Data from the Antiretroviral Treatment Access Studies-II project ('ARTAS-II') as well as site visit and project director reports were used to describe structural factors and best practices found in successful linkage to care programs. Successful programs were able to identify recently diagnosed HIV-positive persons and ensure that a high percentage of persons attended an initial HIV primary care provider visit within six months of enrolling in the linkage program. Results Eight categories of best practices are described, supplemented by examples from 5 of 10 ARTAS-II sites. These five sites highlighted in the best practices enrolled a total of 352 HIV+ clients and averaged 85% linked to care after six months. The other five grantees enrolled 274 clients and averaged 72% linked to care after six months. Sites with co-located HIV primary medical care services had higher linkage to care rates than non-co-located sites (87% vs. 73%). Five grantees continued linkage to care activities in some capacity after project funding ended. Conclusions With the push to expand HIV testing in all U.S. communities, implementation and evaluation of linkage to care programs is needed to maximize the benefits of expanded HIV testing efforts